Front Cover: Homemade Solution of NaOD in D2O: Applications in the Field of Stilbene‐d1 Synthesis (Asian J. Org. Chem. 3/2023). Issue 3 (17th March 2023) - Imai, Keisuke; Tomita, Naohito; Fujioka, Hiroyoshi; Kamiya, Mako; Ogasahara, Riku; Ban, Kazuho; Shimizu, Hyoga; Ishimoto, Takayoshi; Sajiki, Hironao; Akai, Shuji; Sawama, Yoshinari
Abstract : Although NaOD in D2 O is a valuable chemical reagent to prepare the deuterium‐incorporated products, it costs high. The cover picture shows that the simple and cost‐effective preparation of NaOD in D2 O from D2 O and t ‐BuONa was accomplished based on the salting‐out effect. The homemade NaOD in D2 O was used for the one‐pot synthesis of mono‐deuterated trans ‐stilbene (stilbene‐ d 1 ) in the aqueous Horner–Wadsworth–Emmons reaction. The mono‐deuterated trans ‐stilbenes were used to synthesize various deuterated compounds without a loss in the D content. More information can be found in the Research Article by Yoshinari Sawama et al .